Pengaruh ZPT Hormonik Terhadap Produksi Tiga Varietas Cabai Besar (Capsicum annum L.) - Tati Hariyati; Fajwati Fajwati (AGRORADIX : Jurnal Ilmu Pertanian, 2019)
This study aims to determine the effect of growth regulators Hormonik against Parthenocarpy process on three major varieties of pepper plants and to determine the effect of plant growth regulator that is optimum for the process Hormonik Parthenocarpy in three major varieties of chili. This research was conducted in Tanjung Selor, in January to May 2016. The design used in this study is completely randomized design (CRD) with two factors and nine replications. The first factor is the treatment Hormonik consisting of four levels ie 0 cc, 1 cc, 2 cc, 3 cc, the second factor is the variety Arielle, Darmais and Pilar. From the analysis of variance showed that the treatment Hormonik to varieties of very significant effect on the parameters of heavy fruit crop, the number of fruit crops, fruit length persampel and the number of seeds persampel first harvest, after a further test using LSD 5%, by weight of fruit crops and the amount of fruit planting the first crop was not significantly different, but significantly different with persampel fruit length and number of seeds persampel first harvest.